Characterization of DNA ADP-ribosyltransferase activities of PARP2 and PARP3: New insights into DNA ADP-ribosylation - Zarkovic G. (2018)
Fondation ARC (http://www.arc-cancer.net) [PJA20151203415 to A.A.I.]; ERA.Net RUS Plus (www.eranet-rus.eu) [DNA PARYLATION #306 to A.A.I., RFBR-16–54-76010 to O.I.L.]; Ministry of Education and Science of the Republic of Kazakhstan [programs 0115RK02473 and 0115RK03029 to B.T.M.]; NU ORAU (http://www.nu.edu.kz) (to B.T.M.); RSF Grant [14–24-00038 to O.I.L.]; French National Research Agency ‘Labex program’ [ARCANE project ANR-11-LABX-0003–01 to C.S.-P., D.G.]; Fondation ARC Postdoctoral Fellowship (http://www.arc-cancer.net) [PDF20110603195 to I.T.]; CIENCIACTIVA/CONCYTEC Doctoral Fellowship (www.cienciactiva.gob.pe) (to G.Z.). Funding for open access charge: National Laboratory Astana, Nazarbayev University, Astana, Republic of Kazakhstan.